PROSES BERPIKIR ALJABAR SISWA DALAM MEMECAHKAN MASALAH GENERALISASI POLA BERDASARKAN GAYA KOGNITIF - Setyawan, Galuh; Hayuhantika, Diesty (STKIP PGRI Tulungagung, 2018)
This research is aimed to describe algebra thinking of the students in solving problems on pattern generalization in terms of cognitive style of visualizer and verbalizer. This descriptive qualitative research is conducted using questionnaire, tests, and interview. The research subjects used were the students of class VII J, 2 students of cognitive visualizer style and 2 students of cognitive verbalizer style. The results shows, visualizer students on pattern seeking can filter information, on pattern recognizing can finding pattern, on generalizing can generalize general rules. While, verbalizer students on on pattern seeking can filter information, on pattern recognizing can not finding pattern, on generalizing can notgeneralize of the problems. So, students have cognitive style visualizer and verbalizer different in algebraic thinking, visualizer students can passing through all three stages on algebraic thinking, while verbalizer students only to stage on pattern seeking.Â Keywords: algebra thinking, visualizer and verbalizer